La narrativa de Francisco Umbral: 1965-2001. Una lectura - Martínez Rico, Eduardo (Dicenda. Estudios de lengua y literatura españolas, 2003)
The article is a general study on Francisco Umbral’s narrative. From 1965, when he publishes alada de gamberros, to 001, the year of appearence of Un ser de lejanías, the two ooks that mark the time limits of this work. The analysis, nd open clasification of umbralian arrative, has considered the diversity and personal character of these books. ssencial ideas as autobiography, style, Iyric novel, historic novel, literary journalism..., are tudied to describe Umbral arrator, that we can’t separate from Umbral-journalist or mbral-essayist. The article is a journey which starting point re he fundamental narrative ines cultivated by the author.